Burials of possible Romano-British date from Inveresk, East Lothian - Gallagher, Dennis B; Clarke, A; Bruce, M; Barlow, A (Proceedings of the Society of Antiquaries of Scotland, 1994)
Five graves of Romano–British date, possibly associated with the fort or vicus at Inveresk, were revealed during building. The remains of one individual were recovered. There are specialist reports (317 & microfiche) on `Pottery' by Dennis Gallagher, `Human Bone' by Margaret Bruce, and `Animal bone' by Andrew Barlow.